The Emerging Therapeutic Landscape of Advanced Melanoma - Henriques, Vanessa; Martins, Teresa; Link, Wolfgang; Ferreira, Bibiana I. (Current Pharmaceutical Design, 2018)
Melanoma is the deadliest form of skin cancer being responsible for 80% of skin cancer deaths. Furthermore, the incidence of metastatic melanoma has increased over the past three decades with a mortality rate that continues to rise faster than most of all other cancers. The last few years have witnessed an unparalleled change in treatment options for patients with metastatic melanoma by the development of new therapeutic strategies like targeted therapies and immunotherapies that highly improved the patient's prognosis. Despite the paradigm- shifting success of these novel treatments, their effectiveness is still limited by intrinsic or acquired resistance. The objective of this review is to provide an overview of the new available treatment modalities, criteria to select patients who might benefit from a specific therapy, mechanisms of innate and acquired resistance to these treatments and to discuss strategies to overcome drug resistance.
Keywords: drug resistance